Functional dissection of the splice variants of the Drosophila gene homothorax (hth). - Corsetti, E.; Azpiazu, N. (Developmental Biology, 2013)
Homothorax belongs to the TALE-homeodomain family of transcription factors, together with its vertebrate counterparts, the Meis family of proto-oncogenes. It fulfills many important different functions during embryonic and larval developments in Drosophila, which encompass from subdivision and specification of body parts to assembly of heterochromatin structures. Hth interacts with Extradenticle, another member of the TALE-homeodomain family of conserved transcription factors, to facilitate its entrance to the nucleus. The many different functions described for Hth rely on the complexity of the locus, from which six different isoforms arise. The isoforms can be grouped into full-length and short versions, which contain either one or the two conserved domains of the protein (homeodomain and Exd-interacting domain). We have used molecular and genetic tools to analyze the levels of expression, the distribution and the function of the isoforms during embryonic development. Our results clearly show that the isoforms display distinct levels of expression and are differentially distributed in the embryo. This detailed study also shows that during normal embryonic development not all the Hth isoforms translocate Exd into the nucleus, suggesting that both the proteins can also function separately. We have demonstrated that the full-length Hth protein activates transcription of exd, augmenting the levels of exd mRNA in the cell. The higher levels of Exd protein in those cells facilitate its entrance to the nucleus. Our work demonstrates that hth is a complex gene that should not be considered as a functional unit. The roles of the different isoforms probably rely on their distinct protein domains and conformations and, at the end, on interactions with particular partners.